Forced vibration of an axially functionally graded energy pile embedded in temperature-sensitive Winkler soils - Zhang, Zhuanzhuan; Lu, Zhao (Frontiers in Materials, 2025)
In this study, forced vibration analysis of an energy pile with non-uniformity in vertically inhomogeneous soil is presented considering the non-uniform distributed temperature. In establishing the numerical model, it is assumed that the cross-sectional area of the pile remains constant throughout its length, while Young’s modulus and mass density vary along the x direction. The nonlinear soil–pile interaction is modeled with the p–y curve method. Because of the heterogeneity of the soil, the parameter in the p–y curve method changes along the depth direction. The energy pile experiences a complex mechanical load in the working process. In this study, a periodic lateral force and a constant vertical force are applied on the top of the energy pile. The governing equations and the boundary conditions are obtained based on the Hamilton principle. The vibration frequency responses are obtained numerically by using the differential quadrature method. The non-uniformity effects of the pile’s temperature and material inhomogeneity effect are analyzed in detail. Our results demonstrate that the non-uniformity for both the pile and temperature could have significant effects on the vibration frequency response.